Sensitivity of the novel two-point force-velocity model: an assessment of leg muscle mechanical capacities - Djuric, S.; Cuk, I. (Sports Biomechanics, 2022)
The recently proposed two-point force-velocity (F-V) model requires further evaluation in order to develop into a simple tool for muscle mechanical capacities assessment. Therefore, the first aim of this study was to assess the concurrent validity of the proposed model. The second aim of this study was to assess the sensitivity of the proposed model concerning participants of different levels of physical fitness when performing different dynamic tasks. Female elite volleyball players (N = 10; age 22 ± 2 years) and female physical education students (N = 10; age 22 ± 2 years) were tested on maximum countermovement jumps (CMJ) and 6 s maximal cycling sprint (MCS), where manipulation of loads provided a range of F and V data. The assessed F-V relationships were valid in comparison with the standard model. Moreover, the concurrent validity of the maximum force parameter (F0) was high for MCS (r = 0.89) and moderate to low for CMJ (r = 0.43). Sensitivity analysis revealed significant differences between F0 in both leg tests (p < 0.04), along with maximum power parameter in CMJ (p = 0.034) between the groups. The proposed model could provide sport practitioners with a straightforward and very effective tool for assessing muscle mechanical capacities.